Biocompatibility of tricresol formalin: a cyto- and genotoxic analysis in human mononuclear cells: Un Análisis Cito- y Genotóxico en Células Mononucleares Humanas - Oliveira Viera, Fabrício; da Costa Ribeiro, Carlos Eduardo Victor; Montagner, Francisco; Dotto, Sidney Ricardo; da Silva Schmitz, Márcia; Rorato Sagrillo, Michele (Disciplinarum Scientia | Naturais e Tecnológicas, 2025)
Irrigations solutions and techniques did not show evidences of a complete desinfection of root canal system, in pulpar necrosis. Therefore, the use of intracanal medications between sessions is recommended. Cytotoxicity studys did not show convergence of results about the cytogenotoxic effects of tricresol formalin. The goal of this study was to evaluate the biocompatibility of tricresol formalin on PBMC in culture through cell viability, lipid peroxidation, protein carbonylation and DNA damage assays. Twelve human permanent mandibular incisors were used. After endodontic preparation at 11 and 15 millimeters root lenghts, an intracanal tricresol formalin medication was applied, the pulp chamber sealed and the tooth was positioned on a culture well for periods of 24 and 72 hours. The culture medium containing the cells was used as a negative control and as a positive control hydrogen peroxide was used in the medium. The results was tabulated and analyzed by the 1-way ANOVA, followed by the Tukey test. Statistical significance was set at 5%. Tricresol formalin did not show cytotoxicity at the distance of 15 millimeters and in a 24 hour incubation period (P<0,05). At the other distances and times it was considered to be significantly cyotoxic (P<0,05). In 24 hours of incubation, DNA damage was not registered in both lenghts (P <0,05). After 72 hours, the tested solution induced DNA damage in PBMC(P<0,05). Therefore, tricresol formalin demonstrated significant cytotoxicity and genotoxicity, except under very specific conditions of low concentration and short exposure time.